A study of the effects of managers' good character traits and perceived organizational support of employees - Seyedeh Sana Hosseini; Seyedeh Sara Hosseini (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The present study was aimed to investigate the effects of managers' good character traits and perceived organizational support (POS) of employees in one of the therapeutic and educational centers of Kermanshah, Iran. MATERIALS AND METHODS: In this applied, descriptive, correlational, and cross-sectional study, the statistical population included the employees of one of the therapeutic and educational centers of Kermanshah. Besides, Cochran's formula was employed to determine the sample volume (n = 166), and the samples were selected using simple random sampling. As for data collection, the standard questionnaires of managers' good character traits and POS of employees were utilized. To analyze the collected data, the Kolmogorov-Smirnov test and Pearson's correlation coefficient test were used using the SPSS Statistical Software Version 18.0. Moreover, the structural equation approach was employed using SPSS 22 (version 22.0, SPSS Inc., Chicago, IL, USA). RESULTS: The results of the present study demonstrated that managers' good character traits and POS of employees positively and significantly correlated (P = 0.81). In addition, there were positive and significant relationships between each of the components of managers' good character traits and POS of employees, and all hypotheses were supported. CONCLUSION: Overall, the results of the present study showed that managers' good character traits significantly contributed to increasing the POS of employees, thereby increasing the satisfaction with the performance of the therapeutic and educational center.